Nano-hybrid electrospun non-woven mats made of wool keratin and hydrotalcites as potential bio-active wound dressings. Issue 13 (19th March 2019) - Giuri, Demetra; Barbalinardo, Marianna; Sotgiu, Giovanna; Zamboni, Roberto; Nocchetti, Morena; Donnadio, Anna; Corticelli, Franco; Valle, Francesco; Gennari, Chiara G. M.; Selmin, Francesca; Posati, Tamara; Aluigi, Annalisa
Abstract : Keratin/hydrotalcites hybrid nanofibers loaded with diclofenac were proposed as a potential drug delivery system and scaffold for cells growth. Abstract : In this work, nano-hybrid electrospun non-woven mats made of wool keratin combined with diclofenac loaded hydrotalcites (HTD) were prepared and characterized as potential drug delivery systems and scaffolds for fibroblast cell growth. Nano-hybrid electrospun non-woven mats showed a good adaptability to wet skin, effortlessly conforming to the three-dimensional topography of the tissue. Nanosized HTD exercised an overall reinforcing action on the electrospun non-woven mats since the nanohybrid samples displayed a reduced swelling ratio and a slower degradation profile compared to keratin-based nanofiber non-woven mats containing free diclofenac, without negative effects on drug release. The cell viability test indicated a decreased toxicity of the drug when loaded into nanofibers and confirmed the biocompatibility of keratin/HTD electrospun non-woven mats; moreover, a controlled diclofenac release within the first 24 hours does not compromise the fibroblast cell growth in a significant manner.